Pengaruh Pola Kepemimpinan Kiai dan Manajemen Pesantren Terhadap Kinerja Pengurus Pondok: Studi Kasus di Pesantren At-Tadzkir Pasanggrahan Kabupaten Majalengka - Apip, Apipudin; Sukandar, Ahmad; Setiawan, Marwan (Edukasi: Journal of Educational Research, 2022)
The results of the study are: (1) there is a significant influence of the kiai leadership pattern on the performance of the boarding school administrators, (2) there is a significant influence of Islamic boarding school management on the performance of the boarding school administrators, (3) there is a significant influence of the kiai leadership pattern and the pesantren management simultaneously on the performance boarding school administrators, this is indicated by the double correlation coefficient value of 0.571 or the coefficient of determination of 32.60%. Leadership is a conscious effort made by a person (leader) to be able to realize organizational goals through other people by providing motivation so that other people want to carry it out, and for that there is a need for a balance between the individual needs of the implementers. A leader of course must understand and understand the basics of leadership to be able to become a leader, both in a small scope, such as family, discussion leaders, and others as well as leaders in a large scope such as organizational leaders, religious leaders, state leaders and so on. . However, there are several factors for the emergence of leadership: first, the situation and condition factors; second, the ability factor; third, heredity; fourth, the lifting factor; fifth, the factor of interest. This study aims to determine the magnitude of the influence of kiai leadership patterns and pesantren management on the performance of boarding school administrators.